ANALYSIS OF WORK PRACTICES IN ORGANIZATIONS BASED ON ISLAMIC DOCTRINAL STANDARDS REACHES THE WAY FORWARD - Zanirah Mustafa@Busu; Noraını Junoh; Nurul Hidayah Awang @ Ab Rahman; Nurul Izzah Noor Zainan; Mohd Khairul Anuar Ismail; Nor Asmira Mat Jusoh; Norazmila Yusuf; Nik Muniyati Nik Din; Intan Nurul ‘Ain Mohd Firdaus Kozako (Journal of Islamic, Social, Economics and Development, 2022)
Organizations or government agencies are constantly faced with various forms ofthreats either from within or outside the environment and these threats can affect theperformance, productivity and future of an organization. Today, the average threat to anorganization stems from individuals within the organization itself and in turn involves othermembers who damage the identity of the government organization. Typically, these threats areclosely linked to issues of ethics and integrity. Neglect of these two principles can open upopportunities for malpractice, corruption, misconduct and abuse of power in an organization.This article explains the practice of excellent work culture in an organization as stipulated byIslam and applied in the current days. The article exemplifies how Islam stresses on theapplication of excellent work culture and moral values to be practiced in strengthening anorganization. The main purpose of this writing is to identify the elements of work culture inIslam and the characteristics of excellent work culture that every Muslim should know. Apartfrom that, this writing also aims to describe the challenges in implementing Islamic workculture. In the era of globalization, portraying good work ethics among Muslims is essential.Good work ethics are not only about being a diligent, persistent and loyal workforce, but it isalso about being a workforce who integrates Islamic values into their daily life, which do notderail from the values as prescribed in the Qur'an and As-Sunnah. This article also explainshow the concepts, conditions, ethics and characteristics of work culture in Islam remainrelevant and practicable in today’s society. The basis of work culture for Muslim is to seek thepleasure of Allah SWT. The individual’s connection with God shapes their ethical work culture to be extra careful and diligent in their work practices. They will strive to do their best to obtainthe pleasure of God and foster good relationships among their colleagues within theorganization. This article also highlights the need for every Muslim to embrace Shariahcompliantpractices in all aspects of their work. This writing instrumented the qualitativeresearch as its methodology by conducting a library study of the sources of the Quran andhadith as well as scientific materials such as journal articles, reference books from religiousscholars related to the scope of the study topic. The results of this writing can be used as areference and guidance to increase the level of awareness, open the minds of every Muslim aswell as remind each party to fulfill their rights and responsibilities towards every job entrustedto them. Work in the Islamic concept is often associated to the term charity which has a widerscope than simply working for profit or wages. It is hoped that this writing can be used as aguideline or standard for all employees and organizations to work in line with Islamicrequirements.